HE4 and ROMA index in Czech postmenopausal women - Novotny, Zdenek; Presl, Jiri; Kucera, Radek; Topolcan, Ondrej; Vrzalova, Jindra; Fuchsova, Radka; Betincova, Lucie; Rokyta, Zdenek (Anticancer research, 2012)
AIM: The first aim of the project was to evaluate the benefits of the determination of human epididymis protein 4 (HE4) and the risk of ovarian malignancy algorithm (ROMA) index for primary detection of ovarian cancer in a population of Czech women. The second aim was to study the advantages HE4, cancer antigen 125 (CA125) and ROMA index for distinguishing between benign and malignant tumors. Aware of the age distribution of ovarian cancer, we focused on postmenopausal patients. PATIENTS AND METHODS: Our group of patients consisted of 256 females, 21 with ovarian cancer and 235 with benign ovarian tumors. All diagnoses were histologically verified. We determined the serum levels of HE4 and CA125 and calculated the ROMA2 index for postmenopausal women. Serum levels of the analytes were measured using an Architect 1000i instrument. Serum samples were collected prior to surgery or any other form of treatment and the results of the two groups of patients were compared (malignant vs. benign). RESULTS: There was a significant difference in the serum levels for all parameters studied between the groups of patients with malignant and those with benign diagnoses (Wilcoxon test, p<0.0001). When all parameters were evaluated at 95% specificity, the HE4 cut-off was 112 pmol/l at a sensitivity of 71.42%, a positive predictive value (PPV) of 55.56%, a negative predictive value (NPV) of 97.14% and an area under the curve (AUC) of 0.9152. The CA125 cut-off was 81 IU/l at a sensitivity of 80.95%, a PPV of 58.62%, a NPV of 98.23% and an AUC of 0.9731. ROMA2 index had a cut-off 37.70% at a sensitivity of 85.71%, a PPV of 62.06%, a NPV of 98.65% and an AUC of 0.9803. The highest diagnostic efficiency was achieved by the ROMA2 index. CONCLUSION: Determination of HE4 along with CA125 and ROMA2 index calculation is a suitable method for the improvement of the primary detection of ovarian cancer. This approach also improves the differential diagnostic possibilities for distinguishing between malignant and benign tumors.
Keywords: nádory vaječníků; CA-125 Antigen; Female; Age Factors; nemoci ovaria; ženské pohlaví; Ovarian Diseases; postmenopauza; věkové faktory; lidé; Ovarian Neoplasms; membránové proteiny; Proteins; Algorithms; proteiny; antigen CA-125; Czech Republic; algoritmy; Membrane Proteins; Česká republika; lidé středního věku; Postmenopause; Middle Aged; Humans